The effect of estrogen in a man with Parkinson's disease and a review of its therapeutic potential. (1st October 2013) - Adams, Chris; Kumar, Rajeev
<x xml:space="preserve">Abstract</x> Estrogen has been implicated in controlling the pathogenesis and symptoms of Parkinson's disease (PD) in women. Here, we report a 53-year-old male with PD who underwent estrogen therapy with estradiol (E2). Within a month, he exhibited increased dyskinesias. His medication was reduced by 35% from a levodopa equivalent dose (LED) of 820–535 over three months, which overall improved his motor fluctuations and dyskinesias. Therefore, E2 therapy could have therapeutic potential in males with PD.